Raw Multi-Channel Seismic Shot Data from the Southern Ocean and Southeast Indian Ridge acquired during R/V Maurice Ewing expedition EW0114 (2001) ... - Cochran, James; Baran, Janet; Carbotte, Suzanne (Interdisciplinary Earth Data Alliance (IEDA), 2005)
This data set from the Southern Ocean and Southeast Indian Ridge was acquired with the LDEO Multi-Channel Seismic system during R/V Maurice Ewing expedition EW0114 conducted in 2001 (Chief Scientist: Dr. James Cochran). These data files are of SEGY format and include Multi-Channel Reflection Seismic shot data that have not been processed. Data were acquired as part of the project: The Effects of Changes in Mantle Temperature on Melt Supply and Crustal Accretion: An MCS Reflection and OBH Refraction Study of the Southeast Indian Ridge, and funding was provided by NSF grant: OCE99-11720. These data are cited by Baran, 2007 and Baran et al., 2009. ...